Pernikahan Beda Agama Perspektif Pendidikan Islam dalam Sudut Pandang Moderasi Bergama: The Interfaith Marriage in the Perspective of Islamic Education from the Standpoint of Religious Moderation - Mufdlilul Albab; Mokhamad Ali Ridlo (Journal EduMasa Islamic Education, 2023)
The study analyzed the perspective of Islamic education towards interfaith marriage from the standpoint of religious moderation. The research explored the viewpoints of Islamic scholars, contemporary ulama, and legal experts in terms of their interpretation of the Quran and Hadith, as well as examining the Indonesian Marriage Law and other related regulations. The study aimed to provide insights and recommendations on how to address the challenges and opportunities posed by interfaith marriage in a multireligious society.